Dampak Media Sosial Twitter Akun @FiersaBesari pada Gaya Komunikasi Remaja - Dwi Inkasari, Adis; Widodo, Fitri Rahmatillah; Setyarahajoe, Ratna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
The use of social media, specifically Twitter, has a significant impact on teenagers' lives and their communication styles. Teenagers often use Twitter as a platform to share information, photos, videos, tweets, and engage with others through comments and likes. The @FiersaBesari Twitter account is an influential account that shares a variety of content including upset and encouraging quotes, jokes, poetry, and response to current problems. The account is popular among teenagers due to its unique and expressive language style. The research conducted on this topic used descriptive qualitative methods, which involved describing and analyzing the social activities, attitudes, beliefs, perceptions, and thoughts of individuals and groups. The study found that Twitter is widely used by teenagers as a source of the latest information that is easily accessible to anyone. Moreover, the communication style of the @FiersaBesari account is interactive, and it has influenced teenagers to comment using a poetic language style that aligns with Fiersa's unique writing style.